Tax Avoidance Dynamics in Automotive: Sales, Age, Profit, Size Insights: Dinamika Penghindaran Pajak pada Perusahaan Otomotif: Perkembangan Penjualan, Usia Perusahaan, Profitabilitas, dan Ukuran. - Fitria Risky; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the determinants of tax avoidance in the automotive industry, focusing on the influence of sales growth, company age, profitability, and company size. Utilizing a purposive sampling method, a sample of nine automotive companies listed on the stock exchange during the 2015-2018 period was analyzed through secondary data analysis employing Multiple Linear Regression. The results indicate that both sales growth and company age exert a significant impact on tax avoidance in automotive companies. Additionally, profitability demonstrates a partial effect on tax avoidance, while company size also influences tax avoidance within the sector. These findings enhance our comprehension of the factors influencing tax avoidance behavior, offering valuable implications for policymakers, regulators, and stakeholders in promoting tax compliance and transparency within the automotive industry. Highlights: Significant factors: The study identifies sales growth, company age, profitability, and company size as key determinants of tax avoidance behavior in automotive companies. Implications for policymakers: The findings offer valuable insights for policymakers and regulators in enhancing tax compliance and transparency within the automotive industry. Importance of understanding tax avoidance: The study contributes to our understanding of the factors influencing tax avoidance behavior, shedding light on the dynamics within the automotive sector and aiding stakeholders in developing strategies to address tax avoidance effectively. Keywords: Tax avoidance, Automotive industry, Sales growth, Company age, Profitability, Company size.